Composite Hydrogel Spheroids Based on Cellulose Nanofibrils and Nanofibrous Chiral Coordination Polymer by Green Synthesis. (30th September 2020) - Engel, Emile R.; Calabrese, Vincenzo; Hossain, Kazi M. Zakir; Edler, Karen J.; Scott, Janet L.
Abstract: Cellulose‐based hydrogels are promising sustainable materials for a variety of applications, including tissue engineering, water treatment, and drug delivery. However, the tailoring of diverse properties by efficient green chemistry methods is an ongoing challenge. Here, composite hydrogels of consistent spheroidal structure, incorporating TEMPO‐oxidized cellulose nanofibrils and nanofibrous chiral Cu(II) aspartate coordination polymer, are presented. The hydrogels are prepared by a single‐step procedure in aqueous media at ambient temperature and pressure, adhering to the principles of green chemistry. With a view to adapting this method for a variety of alternative coordination polymers (to tailor functional properties), the following critical factors for formation of robust composite hydrogel spheroids are identified: rheological properties of the primary matrix used for spheroidal hydrogel formation and coordination polymer self‐assembly rate. Abstract : The incorporation of coordination polymers into cellulose hydrogels presents an opportunity for tailoring functional properties. Here, robust composite hydrogel spheroids, based on TEMPO‐oxidized cellulose nanofibrils and incorporating a nanofibrous chiral coordination polymer, are prepared in an aqueous medium by a facile green chemistry procedure, where the coordination polymer self‐assembles in situ upon hydrogel formation.